PERAN MAHATMA GHANDI DI BIDANG AGAMA DAN SOSIAL DALAM USAHA KEMERDEKAAN INDIA TAHUN 1914-1947 - Tesa Regenita Putri; Sumiyatun Sumiyatun; Kuswono Kuswono (Swarnadwipa, 2019)
The problem in this research is to analyze the role of Mahatma Ghandi in the field of Religion and Social Affairs in realizing Indian independence. The purpose of this study is to analyze and describe the role of Mahatma Ghandi in realizing Indian independence in the religious and social fields. The research method using historical research methods is a review and other sources that contain information about the past and carried out systematically. Based on the results of research, in the field of Religion, Ghandi's life journey studied other religions as a reference because it can instill a sense of belief in religion, besides Ghandi also believes that the Almighty God is the basis of all religions according to Gandhi, is also a thestarting point of all religions. By mentioning religion, Gandhi pointed to it not formally and traditionally, but rather something that underlies all religions that will bring us to meet God. In the social sphere, Gandhi's Teachings flow with them together in the social life of the Indian people. Gandhi's main thoughts are summarized in a span of history and history in the midst of the struggle of the Indian people. Mahatma Ghandi played a role in realizing Indian Independence in the Religion and Social Fields through his teachings, Gandhi in carrying out resistance actions always put forward human values as the basic basis of his movement. Gandhi's teachings flowed together in the social life of the Indian people. Gandhi's main thoughts are summarized in a span of history and history in the midst of the struggle of the Indian people, for future researchers, it is hoped that Mahatma Ghandi's research in politics, economics and others will be further developed in order to realize Indian independence.Keywords: The Role of Mahatma Gandhi, Religion, Social Affairs